Dictyostelium transposable element DIRS-1 has 350-base-pair inverted terminal repeats that contain a heat shock promoter. - Zuker, C (1984)
DIRS-1 is a 4.7-kilobase-pair repetitive and apparently transposable Dictyostelium genetic element that is transcribed during differentiation or after heat shock. The terminal regions of DIRS-1 are inverted repeats of 330 base pairs. The repeats are highly conserved both within a given element as well as between different members of the family (less than 10% divergence). At the distal end of all left repeats is a 32-nucleotide sequence composed almost entirely of A and T residues. In addition to this 32-base A + T sequence, the distal region of all right repeats is extended by a 28-base-pair A + T-rich sequence that is identical in all copies. The sequences flanking each DIRS-1 sequence are completely dissimilar, and there appears to be no duplication of the genomic DNA sequence at the presumed point of DIRS-1 insertion. The terminal repeats can also be found interspersed in the genome independently of the complete element. In addition, the terminal repeats carry a 15-nucleotide sequence that greatly resembles the Drosophila consensus heat shock promoter and may be involved in the transcriptional induction of the DIRS-1 sequences.